Буквальная и реальная равнозначность предложений - Виноградов, М. Ф. (Kalbotyra, 1991)
The paper is aimed at showing that the conceptions of surface and communicative meanings employed in current sentence analysis ant more complex and heterogeneous than we used to think. Interpretation of surface and communicative meanings as complex entities makes it possible to see the hierarchy of semantic components in the sentence meaning, dependence of sentence proposition upon some factors of social interaction and on this basis to establish various types of sentence equivalence.